A STYLISTIC ANALYSIS OF SYNTACTIC STRUCTURES IN THE DIALOGUES OF 12 ANGRY MEN (1957) - Rifki Adriansyah; Firna Hijharianti Arditha; Nafilah Nafza Islami; Salman Al Farezel; Mutmainnah Mutmainnah (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
This study aims to analyze the syntactic structures found in the dialogues of the film 12 Angry Men (1957) from a stylistic perspective. The research focuses on three syntactic aspects, namely sentence length (simple and complex sentences), sentence types (interrogative and imperative forms), and repetition. The data were obtained from selected dialogues in the film and analyzed using a qualitative descriptive method. The results show that syntactic structures function not only as grammatical forms but also as stylistic devices that contribute to characterization, power relations, and the development of argumentative tension among the jurors. Simple sentences are predominantly used to express strong opinions, emotional responses, and prejudice, while complex sentences are employed to convey logical reasoning and reflective arguments, particularly by Juror #8. Furthermore, interrogative and imperative sentence forms are frequently used indirectly to control the discussion and influence other characters. Repetition is utilized to emphasize key ideas, highlight psychological conditions, and reinforce central legal concepts such as reasonable doubt. This study concludes that syntactic variation plays a crucial role in constructing meaning and realism in film dialogue. The findings are expected to contribute to linguistic and stylistic studies, especially in the analysis of language use in cinematic discourse.